Wage Moderation in Crises : Policy Considerations and Applications to the Euro Area - Decressin, Jorg (Staff Discussion Notes; Staff Discussion Notes, 2015)
The paper studies the impacts of wage moderation in the euro area. Simulation results show that if a single euro area crisis-hit economy undertakes wage moderation, the impact on output is positive for that economy and for the entire euro area. If all crisis-hit economies undertake wage moderation together, their output still expands, albeit to a lesser degree. If the wage moderation is accompanied by cuts in policy interest rates by the central bank-and by quantitative easing once interest rates hit the zero lower bound-then output for the entire euro area expands as well.